(3HgLI GdeLGdS hCfS GdeLGdSs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3bGd (B: (3hbO LeYJ ai cJGHi gPG ef GdCeKGd GdSGFQI , hGdCHjGJ GdfGOQI , hGdMce GdHGdZI , hGdMcGjGJ GdeeJfYI ai afhf cKjQI , ef eYGfi GdOjf hGdOfjG eG GfJgi Edjg MaXi QYGjJi , hVeJg QhGjJi hYfGjJi s
(3BNQgG (B:s
(3KbI HGdPi dOjc ef GdSJQ adG JMRfi dOi jhe fTQ jhe gJc GdSQhQ Yf MLH GdZjH adG JgJc ddfGS SJQi s
(3HCdhgG agQSJ dcd eG hQO HgG ef CHhGHs
(3hGfXQ GdLRA GdChd HGdQbGe (B98(3,(B99(3,(B100(3COHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B315s
(3GdLRA (B1 - (3U (B208 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B129 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs